AFM monitoring of the cut surface of a segmented polyurethane unveils a microtome-engraving induced growth process of oriented hard domains. (March 2023) - Gojzewski, Hubert; van Drongelen, Martin; Imre, Balazs; Hempenius, Mark A.; Check, Casey; Chartoff, Richard; Wurm, Frederik R.; Vancso, G. Julius
Abstract: We report on nanoscale order-disorder transitions of hard segments and their domains composed of 4, 4′-methylenebis(phenyl isocyanate) - 1, 4-butanediol (MDI-BD), in polycaprolactone-based ( M n  = 2000 g/mol) polyurethanes (PCL-PUs), when the free surface is pre-oriented by cryo-microtoming of the material. Morphological variations of the hard domains as a function of temperature and the anisotropy of surface morphology features are captured by employing Atomic Force Microscopy (AFM) stiffness imaging by PeakForce Quantitative Nanomechanical Mapping (PF-QNM). The AFM imaging is supported by WAXS, SAXS, FTIR, and DSC measurements. The experimental results show that hard domains initially grown at the surface break apart at elevated temperatures (65 °C) and cannot be re-grown upon cooling. They require new microtoming to repeat the growth scenario. The detailed step-by-step submicron scale observations of the surfaces serve to show importance of the influence that microtoming and the time after its completion have on surface morphology, and that these shall be considered when studying polymer materials microscopically. Highlights: Dis-/order transitions of hard domains in polycaprolactone-based polyurethanes are observed by AFM at different temperatures. Surface anisotropy introduced by cryo-microtoming initiates oriented growth of hard domains. Hard domains break apart at elevated temperatures (65 °C), but cannot be re-grown upon cooling (process inversibility). Study highlights the relevance on the sample preparation for polymer microscopies.